Relationship between body conformation & fittness of racing horses - Al-Khazragii, S. A.; Jawad, N. M. (The Iraqi Journal of Veterinary Medicine, 1999)
This study was designed to investgate - The Conformation and its effect on The Performance of the Arabian horses, aged (4-6) years in Iraq“. This research was perfomed in different regions for 193 horses. The age and sex of the horses were fixed. The anatomical structures were noticed. The symmetrical in size of joints and hooves in case of standing position, normal walk, trotter and the running were observed. The clinical examination was done by the palpation of fore limbs from the shoulder joints till the sole of the hoof. The examination of the hind limbs was performed also from the hip jointtill the sole The conformation measurements were recorded on 188 Arabic horses which were classified into two principle. The first class includes the racing horses while the classes . Second class was not sharing the races. The horses with aquired abnormal conformations were also registed. The analysis of variance (A.N.O.V.A) in between different groups revealed significant differences of P < 0.05,P<0.001 This significant differences was done to the difference in age, six, management, training and environment. Further more, the results of this study detected that the conformation measurements of Arabic horses in Iraq conceded with the measurements registed by other researchers.